1970
DOI: 10.3329/bmrcb.v37i2.8433
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about inhaler use among the chronic asthma patients in selected hospitals

Abstract: This cross sectional descriptive study was conducted among the chronic asthma patients attending three Institutes of Dhaka city namely National Asthma Center, The National Institute of Diseases of Chest and Hospital (NIDCH), Mohakhali, and Dhaka Medical College Hospital to assess the level of knowledge regarding inhaler use. Convenient sampling was adopted. Data were collected using one semi-structured questionnaire through face-to-face interview. The patients were aged from 18 to 75 years with mean age being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Consequently, average self-care practice score is slightly high found in this study results. Parvin et al, found that maximum respondents were suffering from asthma for 5-10 years which is congruent with this study finding 14 . Moreover, self-care practice researched in other studies revealed that self-care practice can reduce asthma symptoms, prevent asthma triggers, and increase adherence with medication regimens 15,16 .…”
Section: Self-care Practice Of Asthmatic Patientssupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, average self-care practice score is slightly high found in this study results. Parvin et al, found that maximum respondents were suffering from asthma for 5-10 years which is congruent with this study finding 14 . Moreover, self-care practice researched in other studies revealed that self-care practice can reduce asthma symptoms, prevent asthma triggers, and increase adherence with medication regimens 15,16 .…”
Section: Self-care Practice Of Asthmatic Patientssupporting
confidence: 91%
“…One study found that there is a small positive correlation between knowledge and self-care practice in asthma (r = 0.24, p<0.01) 19 . One other study illustrated that awareness of the patients' knowledge and practice of controlling and preventing the disease is important for planning health education activities 14 . To sum up, the study result indicated that the study independent variable "knowledge" is associated with dependent variable "self-care practice" in asthmatic patients at Rajshahi in Bangladesh.…”
Section: Relationships Between Knowledge Attitude and Self-care Pramentioning
confidence: 99%
“…and patients not willing to participate in the study. A standardized questionnaire which included sociodemographic data (Age, sex, occupation, education status, socio-economic status etc) knowledge regarding the disease and use of inhalers, attitudes toward use of inhalers and practices regarding inhaler use and observation checklist for technique of using inhalers was developed from questionnaire which have been used in earlier studies and was modified by asthma experts [10][11][12][13][14][15] . The questionnaire was validated and pretested on a group of bronchial asthma patients.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…A study conducted in India reported that 64% of adults suffering from respiratory diseases and prescribed Metered Dose Inhalers (MDIs) used them incorrectly while 25.9% of adults with respiratory diseases who were prescribed rotahalers used them incorrectly 9 . A study in Bangladesh shows that only 35.8 per cent asthma patients could demonstrate the technique of inhaler use properly 10 . Asthma cannot be cured but attacks of asthma and associated complications can be prevented by proper management plan 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation